CB-FMEA: Adapting the Failure Modes and Effects Analysis to Assess Failures in Community Settings - Tessema, Tselot; Montague, Enid (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
This study introduces the Community-Based FMEA (CB-FMEA), a novel adaptation of Failure Modes and Effects Analysis (FMEA) designed to identify system failures in community settings. Traditional FMEA tools overlook contextual and environmental risk factors, such as social, psychological, economic, legal, and technological factors, which significantly impact healthcare access and delivery. Cardiologists were interviewed to explore contextual factors affecting cardiovascular care access and management. Interview data informed a patient journey process map and populated a traditional FMEA table, revealing key failures linked to SDOH (e.g. education, income, stress). Findings highlight the limitations of the conventional FMEA in capturing contextual factors leading to socio-psychological harm. The proposed CB-FMEA adaptation integrates participatory methods, qualitative insights, and a contextual risk assessment. Future research will expand stakeholder participation (e.g., patients, family physicians) and consider how to incorporate field notes into the CB-FMEA process.